2014
DOI: 10.1108/pijpsm-07-2012-0064
|View full text |Cite
|
Sign up to set email alerts
|

Community support for license plate recognition

Abstract: Purpose -Although the use of license plate recognition (LPR) technology by police is becoming increasingly common, no empirical studies have examined the legal or legitimacy implications of LPR. LPR may be used for a variety of purposes, ranging from relatively routine checks of stolen vehicles to more complex surveillance functions. The purpose of this paper is to develop a "continuum of LPR uses" that provides a framework for understanding the potential legal and legitimacy issues related to LPR. The paper t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Previous research has shown complicated findings about the relationship between police and their communities regarding LPRs. The public remains fairly unaware of LPR use in their communities, and when they are aware, they are supportive of certain types of LPR uses more than others (Merola and Lum, 2012;Merola et al, 2014). In particular, previous community surveys on LPRs suggest the public is less supportive of using LPRs for everyday traffic and parking violations, but more supportive of using LPRs to solve serious crimes.…”
Section: Rapid Diffusion Of License Plate Readersmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown complicated findings about the relationship between police and their communities regarding LPRs. The public remains fairly unaware of LPR use in their communities, and when they are aware, they are supportive of certain types of LPR uses more than others (Merola and Lum, 2012;Merola et al, 2014). In particular, previous community surveys on LPRs suggest the public is less supportive of using LPRs for everyday traffic and parking violations, but more supportive of using LPRs to solve serious crimes.…”
Section: Rapid Diffusion Of License Plate Readersmentioning
confidence: 99%
“…Although limited by the data they access and by the frequency and ways they are used (see discussions by Association of Chief Police Officers, 2013; Lum et al, 2010), LPRs are believed by law enforcement officials to be a force-multiplier to many crime prevention and homeland security efforts. At the same time, LPRs present specific challenges and controversies related to data privacy, data storage and systems maintenance (Merola et al, 2014). Thus, in light of their rapid diffusion, how LPRs are used and their effectiveness in achieving goals of both police and citizens should be central concerns to police practice and research.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have tried to monetize these sorts of costs. Merola, Lum, Cave and Hibdon (2014), for example, tried to get at some of the social costs of LPRs, such as privacy and community trust, by using a community survey. The authors found that the public’s views about the use of these devices depended in part on the purposes for which they were deployed.…”
Section: What Is Left Unattended?mentioning
confidence: 99%
“…We do not know how long police should retain records before purging them. Some research has suggested that the public might support long-term record retention (Merola et al 2014). We need research on the time between a data collection and when police realized that they needed the information.…”
Section: Big Data and Concerns About Surveillance And Disparate Impactmentioning
confidence: 99%